A dynamic response analysis of a multi-story reinforced concrete building - Mallonga, Rosalio Arizabal (1978)
This thesis as an attempt to check out the design of a multi-storey reinforced concrete building by carrying out a dynamic response analysis and an energy absorption capacity of the building elements. The particular model used in this research is the ABC Building that was damaged during the August 2, 1698 earthquake. Analyzing the building as a shear framed structure, effort for mathematical model formulation was made using the data from the Ruby Tower Earthquake of August 1968 furnished by the PAGASA and from the AIT DIsk No. 9. Comparison was made between the base shear values from SEAOC22 and the results from the dynamic response analysis: 1. The determination of the static base shear in both directions using SEAOC; 2. The dynamic response analysis. The properties of the ABC Building were utilized in generating the stiffness matrix. The stiffness matrix used was through the courtesy of Dr. Salvador F. Reyes, U.P. College of Engineering. With the stiffness matrix known, the values of W2 were solved from the matrix equation: (K - w^2m ) x = 0. To solve this equation, the Subroutine N-Root was utilized as the frequencies (wsn) are actually the eigenvalues of the stiffness matrix. The Subroutine N-Root is from the IBM/S 360 Library. The mode shapes, (0in) were likewise solved. With the values of the frequencies known the periods of vibration (T),were solved. The values of the spectral velocity, Sv, spectral acceleration, Sa and spectral displacement Sd, were then obtained from graphs properly drawn for this purpose, and selecting the desired damping factor. These information was obtained from the AIT Disk No.9 which were likewise stored in a disk at the U.P. Computer Center. These values were later made the input data in determining the response of the structure and also in calculating the dynamic forces.